ADVANTAGES OF HYSTERECTOMY BY VAGINAL ROUTE COMPARED TO OTHER METHODS: SYSTEMATIC REVIEW - Cabral Barbosa, Alice; de Oliveira Arantes, Arthur; de Almeida Sousa, Jéssica; Carolina Rios Fonseca, Maria; Mitsue de Castro Matsuoka, Sarah (Health and Society, 2022)
The aim of this research is to present the surgical technique of vaginal hysterectomy (VH) and discuss its advantages over other techniques. The work method was an integrative literature review, associating “hysterectomy” and “vaginal route/way”. There were included 7 original articles, available in full, in the Portuguese, English and Spanish languages, published between 2000 and 2018, in the PubMed, SciELO and Lilacs databases. The study showed the anatomical characteristics of the uterus and the most used surgical technique in HV. The advantages of vaginal route in relation to other techniques have been described, among which the following should be highlighted: minimal invasion, lower incidence of complications and absence of visible scars. In contrast, also were reported the disadvantages and limitations. In summary, HV is a great option for uterine removal, and should be part of the therapeutic arsenal of gynecological surgeons, since its advantages outweigh the disadvantages described in the literature.